Detection of Landmines by Neutron Backscattering: Effects of Soil Moisture on the Detection System - Baysoy, D. Y.; Subasi, M. (AMER INST PHYSICS, 2009)
Detection of buried land mines by using neutron backscattering technique (NBS) is a well established method. It depends on detecting a hydrogen anomaly in dry soil Since a landmine and its plastic casing contain much more hydrogen atoms than the dry soil, this anomaly can be detected by observing a rise in the number of neutrons moderated to thermal or epithermal energy But, the presence of moisture in the soil limits the effectiveness of the measurements. In this work, a landmine detection system using the NBS technique was designed A series of Monte Carlo calculations was carried out to determine the limits of the system due to the moisture content of the soil. In the simulations, an isotropic fast neutron source ((252)Cf, 100 mu g) and a neutron detection system which consists of five (3)He detectors were used in a practicable geometry In order to see the effects of soil moisture on the efficiency of the detection system, soils with different water contents were tested.
Keywords: landmine; back scattered neutrons; (252)Cf; ANTI-PERSONNEL LANDMINES; SCATTERING; Physics